PERAN ARSIP DALAM MENDUKUNG UPAYA DIPLOMASI GUNA PENYELESAIAN SENGKETA PERBATASAN CAMAR BULAN DAN TANJUNG DATU: Array - Purwo Mursito (Jurnal Kearsipan, 2010)
Indonesia and Malaysia have worked out for peaceful settlement of dispute on their border at Camar Bulan and Tanjung Datu. This paper focuses on the role of archives in resolving the dispute. The availability of comprehensive archives related to the border dispute, such as agreement and cartography is absolutely necessary. Research Methodology used in this paper is a library study followed by discussions on the archives’ role related to the issue. Malaysia’s claim over Camar Bulan and Tanjung Datu was based on MoU 1975 signed in Kota Kinabalu and MoU 1978 in Semarang. However, the MoU was a temporary agreement (modus vivendi) and there was not enough explanation on the reason that Indonesia did not fail any complaints.